Discipline and intergenerational transmission - Bub, Samantha.; Snyder, Aria (My University, 2008)
The disciplinary practices that parents use on their own children affect the child throughout his or her life and influence the discipline that they plan to use with their children. This study investigated attitudes about intergenerational transmission of corporal punishment and nonphysical means of discipline by surveying 100 male and female college students ages 18-26 years of age at a Midwestern college. It was hypothesized that college students would plan to discipline their own children the same way they were disciplined as children based on the Social Learning Theory. Survey data was analyzed using frequencies, cross-tabulations, and a reliability analysis. Results indicated the majority of participants will use similar discipline practices as their parents. These results confirmed the hypothesis and were supported by the literature. Implications for practitioners include there needs to be parenting classes that address effective discipline practices. Suggestions for replication and future research are discussed.
Keywords: Corporal punishment; Intergenerational transmission; Discipline practices; Parenting; Discipline of children; Child rearing